Deficiency of cholesterol 7α‐hydroxylase in bile acid synthesis exacerbates alcohol‐induced liver injury in mice - Donepudi, Ajay C. (Hepatol Commun, 2017)
Alcoholic fatty liver disease (AFLD) is a major risk factor for cirrhosis‐associated liver diseases. Studies demonstrate that alcohol increases serum bile acids in humans and rodents. AFLD has been linked to cholestasis, although the physiologic relevance of increased bile acids in AFLD and the underlying mechanism of increasing the bile acid pool by alcohol feeding are still unclear. In this study, we used mouse models either deficient of or overexpressing cholesterol 7α‐hydroxylase (Cyp7a1), the rate‐limiting and key regulatory enzyme in bile acid synthesis, to study the effect of alcohol drinking in liver metabolism and inflammation. Mice were challenged with chronic ethanol feeding (10 days) plus a binge dose of alcohol by oral gavage (5 g/kg body weight). Alcohol feeding reduced bile acid synthesis gene expression but increased the bile acid pool size, hepatic triglycerides and cholesterol, and inflammation and injury in wild‐type mice and aggravated liver inflammation and injury in Cyp7a1‐deficient mice. Interestingly, alcohol‐induced hepatic inflammation and injury were ameliorated in Cyp7a1 transgenic mice. Conclusion: Alcohol feeding alters hepatic bile acid and cholesterol metabolism to cause liver inflammation and injury, while maintenance of bile acid and cholesterol homeostasis protect against alcohol‐induced hepatic inflammation and injury. Our findings indicate that CYP7A1 plays a key role in protection against alcohol‐induced steatohepatitis. (Hepatology Communications 2018;2:99–112)